ETHICS AND VALUES EDUCATION THROUGH ANTHROPOMORPHISM IN EAST NUSA TENGGARA FOLKTALES - Gracia M N Otta (Englisia: Journal of Language, Education, and Humanities, 2018)
This study describes anthropomorphism that contains ethics and values education within East Nusa Tenggara folktales in Indonesia. The study explored the data on anthropomorphism based on the studentsâ€™ textbooks of the local content subject, â€œPengetahuan Lingkungan dan Sosial Budaya Daerah Nusa Tenggara Timur Sekolah Dasar Kelas 2â€ andâ€œCerita Rakyat Nusa Tenggara Timur Sekolah Dasar Kelas 6â€. The textbooks containing the folktales were published in 2012 by CV Jala Makmur â€“ Kupang. There were 20 folktales in the textbooks, but the anthropomorphisms investigated were only within four folktales, in which the animals behaving like human beings. The study was library research based, using a descriptive qualitative method. The study applied a moral approach since the value of anthropomorphism is to educate the readers. The results of this study showed that there were eight values to learn in Hoga Woe, three in Nenek Bupu Repu, five in Asu Nok Maleobibi, and five in Dhone dan Kaju. This study concludes that folktales can be one of the teaching and learning materials for introducing morals, attitudes, and good judgments to the young students in ethics and values education. In addition, folktales can be developed into plays, from which the students can play the characters in order to easily absorb moral education in a fun and interesting way.